Career Identity Development of “Dependent” Immigrant Women: A Qualitative Exploration - Rastogi, Deepika (Université d'Ottawa / University of Ottawa, 2018)
The purpose of the proposed study was to understand the process of career identity development among women immigrants arriving as applicants with dependent status, where career identity refers to a generalized perception of one’s career-related interests and potential in terms of acceptable career roles. Previous research has shown that the majority of dependent applicants under the economic class of immigrants are women and constitute a group of talented persons, possessing the skills to contribute positively to Canada’s economy. However, immigrant women who arrive on a dependent visa to Canada have largely been ignored within immigrant literature. Exploring their career-related experiences upon immigration may assist in understanding the effect of these experiences on their developing career identity. This in turn may lead to useful information in terms of how to tap into their potential and help them realize their career goals, within an evolving process of career development. Adopting a constructivist approach, a qualitative enquiry inspired by a grounded theory methodology was carried out to identify some of the key themes relevant to immigrant women’s career identity development and possible interactions between those themes. Purposive and snowball sampling were used to recruit six participants for the study. Semi-structured interviews with open-ended questions were conducted with each participant. Data were analyzed using Braun and Clarke’s (2012) six-phase method of conducting thematic analysis to generate themes and subthemes. Eight main themes were generated and include: On board the Canadian dream, Coming to terms with “dependent” status, Maintaining equilibrium, Tipping point, Grieving the loss of preferred career trajectory, Taking agency, Redirecting one’s career path, and Emergence of a strengthened career identity. Findings from the study shed light on some of the gender-specific experiences that women immigrants undergo in their career journey, and may provide useful information to career counsellors who play a critical role in helping immigrants navigate through career transitions in a new country.
Keywords: Career identity; Dependent immigrants; Qualitative